Setting the Tone for Corporate Social Responsibility in Kenya- What Does the New Mining Act Have to Say? - Cowell, Kelly (Department of Public Law, 2019)
Motivated by the abundance of unexploited natural resources within Kenya, the country released a new Mining Act in 2016. The proclaimed objective, to increase mineral contribution from one percent to ten percent of Kenya’s GDP by 2030, demonstrates governmental focus on enticing investment in the mineral sector. Historically, a primary focus on investment potential in developing countries exposed to sudden mineral booms, is likely to lead to social and environmental destruction. It is therefore important to evaluate the status of Kenya’s new mineral law, and what that means for the country’s ability to foster a sustainable future. Corporate social responsibility (CSR) is discussed in relation to international norms and standards. Kenya’s Constitution and new Mining Act are then examined to identify what safeguards ensure social and environmental protection. While many countries have voluntary CSR mechanisms, Kenya’s Mining Act contains mandatory CSR procedures and regulations. Should Kenya fail to ensure these laws are adhered to within the spirit of the Constitution, there will be negative consequences for the country. Whether there is sufficient governmental willpower, combined with the necessary human and technological resources, to maintain and enforce the established laws is yet to be determined.